2020
DOI: 10.1093/neuonc/noaa215.227
|View full text |Cite
|
Sign up to set email alerts
|

Ctni-61. Pilot Study of Repeated Planned Glucarpidase Following High Dose Methotrexate (Hd-Mtx) in CNS Lymphoma (Cnsl)

Abstract: This study explores the repeated use of glucarpidase following HD-MTX in patients with CNSL. HD-MTX requires aggressive hydration and inpatient monitoring to prevent toxicity. Glucarpidase 50 units(u)/kg for delayed MTX clearance results in a reduction of systemic MTX levels without crossing the blood brain barrier. This study explores the use of 1000 or 2000 units of glucarpidase following repeated cycles of MTX 3–8 g/m2. Eligible adult patients had isolated CNSL, CrCl ≥ 60 mL/min, and KPS ≥ 50. Rituximab wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similarly, a recent cohort by Li et al has reported that a higher MTX dose (HD-MTX dose of 8 g/m2) is signi cantly associated with better clinical response rates and higher progression free survival in managing PCNSL [40]. An ongoing study using scheduled glucarpidase with HD-MTX may facilitate administering higher doses of MTX while minimizing side effects that may result from HD-MTX [41]. The increasing incidence of elderly PCNSL demands trials speci cally targeting this patient population to facilitate delivering higher therapeutic doses of methotrexate in elderly patients without compromising their renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent cohort by Li et al has reported that a higher MTX dose (HD-MTX dose of 8 g/m2) is signi cantly associated with better clinical response rates and higher progression free survival in managing PCNSL [40]. An ongoing study using scheduled glucarpidase with HD-MTX may facilitate administering higher doses of MTX while minimizing side effects that may result from HD-MTX [41]. The increasing incidence of elderly PCNSL demands trials speci cally targeting this patient population to facilitate delivering higher therapeutic doses of methotrexate in elderly patients without compromising their renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The role of site-specific therapy for patients with leptomeningeal or ocular involvement of primary CNS lymphoma remains controversial. High-dose IV methotrexate achieves cytotoxic concentrations in the CSF 20 and vitreous space, 21 obviating the need for direct intrathecal or intraocular administration. Increasingly, many practitioners reserve intrathecal chemotherapy for persistent or refractory leptomeningeal disease.…”
Section: Primary Central Nervous System Lymphomamentioning
confidence: 99%
“…In addition, HD-MTX must be monitored with dose reduction schedules based on the urinary clearance rate before each treatment cycle [ 63 ]. As a last resort, glucarpidase (carboxypeptidase-G2) can be used to reduce very rapidly an important increase in the serum concentration of methotrexate [ 64 ].…”
Section: Treatmentmentioning
confidence: 99%